A rare case: ileo-ileal intussusception with acute appendicitis - Raja, Raadhika; Sreeramulu, P. N.; D., Srinivasan; R., Rahul Singh (International Surgery Journal, 2018)
The occurrence of intussusception and appendicitis in the same patient has seldom been described in the pediatric population. Authors report a case of two- level ileo- ileal intussusception associated with acute appendicitis. A 2-year-old boy presented with colicky abdominal pain, vomiting and non-passage of stools and flatus since 4 hours. On physical examination, he was irritable and restless. Abdomen was distended, borborygmi was heard on auscultation, ultrasound of abdomen suggested ileocolic intussusception. Emergency laparotomy was performed and an ileoileal intussusception was visualized and was reduced manually. After reduction, appendix was visualized, and it was found to be inflamed and elongated. Appendectomy was performed. Authors present this case because of its rarity in occurrence in a toddler in a rural setup as ours.